2021
DOI: 10.1371/journal.pcbi.1009280
|View full text |Cite
|
Sign up to set email alerts
|

A hidden Markov model reliably characterizes ketamine-induced spectral dynamics in macaque local field potentials and human electroencephalograms

Abstract: Ketamine is an NMDA receptor antagonist commonly used to maintain general anesthesia. At anesthetic doses, ketamine causes high power gamma (25-50 Hz) oscillations alternating with slow-delta (0.1-4 Hz) oscillations. These dynamics are readily observed in local field potentials (LFPs) of non-human primates (NHPs) and electroencephalogram (EEG) recordings from human subjects. However, a detailed statistical analysis of these dynamics has not been reported. We characterize ketamine’s neural dynamics using a hidd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Hence, models of propofol anesthesia have the potential to provide tremendous insights into the biology of coma. Unlike propofol, recordings during ketamine anesthesia show alternating high frequency (Gamma) oscillations and oscillations that are coordinated across the cortex from frontal to occipital regions [64]. At low doses, however, ketamine primarily only acts in the inhibitory interneurons leading to fast oscillations.…”
Section: Doc and General Anesthesiamentioning
confidence: 99%
“…Hence, models of propofol anesthesia have the potential to provide tremendous insights into the biology of coma. Unlike propofol, recordings during ketamine anesthesia show alternating high frequency (Gamma) oscillations and oscillations that are coordinated across the cortex from frontal to occipital regions [64]. At low doses, however, ketamine primarily only acts in the inhibitory interneurons leading to fast oscillations.…”
Section: Doc and General Anesthesiamentioning
confidence: 99%
“…Ketamine is a fast acting anesthetic, with a distribution half-life of only 10–15 min ( Li and Vlisides, 2016 ). We and others have shown that an anesthetic dose of ketamine induces fast transient changes in EEG signals that is characterized by alternating slow delta oscillations and gamma oscillations ( Akeju et al, 2016 ; Garwood et al, 2021 ; Li and Mashour, 2019 ; Schwartz et al, 1974 ). The objective of the current study was to use high-density EEG signals that directly measure neural activity at high temporal resolution to investigate the dynamic brain states and their reconfigurations during altered states of consciousness induced by ketamine.…”
Section: Introductionmentioning
confidence: 95%
“…ere is also a 40% chance that he will need to go to the library to find reference material. en, depending on his understanding of the class content, he has a 20%, 40% and 40% chance to return to the first, second and third classes to continue his studies [9][10][11][12][13][14][15].…”
Section: Markov Modelmentioning
confidence: 99%